Rhabdomyosarcoma of the common bile duct: an unusual cause of obstructive jaundice in a child - Kırlı, Elif Altınay; Parlak, Erkan; Oğuz, Berna; Talim, Beril; Akçören, Zuhal; Karnak, İbrahim (The Turkish Journal of Pediatrics, 2012)
Biliary rhabdomyosarcoma (RMS) is a rare malignancy of childhood. The radiological findings and clinical presentation of the tumor can mimic an entirely different pathology. The incidence of RMS has impeded the development of a standardized form of treatment. A four-year-old child with botryoid RMS in the common bile duct is reported herein to emphasize the role of surgery in the small-sized tumor and the role of endoscopic retrograde cholangiopancreatography (ERCP) in the diagnosis and relief of biliary obstruction before total excision.